2019
DOI: 10.1002/acr.23615
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Systolic Extinction Training in Fibromyalgia Patients With Elevated Blood Pressure Response to Stress: A Tailored Randomized Controlled Trial

Abstract: SET resulted in statistically significant, clinically meaningful, and long-lasting pain remission and interference compared to the OT-TENS and AE-BRT. These results suggest that BRS modification was the primary mechanism of improvement. Replication with larger samples and extension to other chronic pain conditions appears to be warranted. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…Painful and non-painful stimuli during the systolic and diastolic phases of the cardiac cycle decreases clinical pain and pain sensitivity. A preliminary study has demonstrated that the experimental protocol used as a baroreflex training, in combination with operant behavioral therapy, can activate inhibition in various components of the pain network [ 70 ]. Restoring BRS, known to be depreciated in FM, and sympatico-vagal balance seem to be linked by classical and operant conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Painful and non-painful stimuli during the systolic and diastolic phases of the cardiac cycle decreases clinical pain and pain sensitivity. A preliminary study has demonstrated that the experimental protocol used as a baroreflex training, in combination with operant behavioral therapy, can activate inhibition in various components of the pain network [ 70 ]. Restoring BRS, known to be depreciated in FM, and sympatico-vagal balance seem to be linked by classical and operant conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…A behavioural pain treatment with neuromodulator called "Systolic Extinction Training" (SET) that combines operant behavioural pain therapy (OBT) and cardiac-gated electrical baroreceptor training could reactivate baroreflex sensitivity and reprogram the brainstem in female patients with fibromyalgia. Long-term effects of 12 months after a 20hours SET showed pain freedom in 82% of the patients [12]. We hypothesize that a patient with an inflammatory rheumatic disease such as rheumatoid arthritis can also reactivate their baroreflex sensitivity and influence pain perception by the behavioural neuromodulator methods such as the SET.…”
Section: Introductionmentioning
confidence: 91%
“…Bezüglich verschiedener psychologischer Verfahren liegen inzwischen systematische Übersichtsarbeiten von randomisierten kontrollierten Studien zu achtsamkeitsbasierter Stressreduktion [42], Biofeedback [43], Hypnotherapie [44] und kognitiven Verhaltenstherapien (live, internetbasiert) [45,46] vor. Die systematischen Übersichtsarbeiten belegen eine Wirksamkeit der Verfahren auf mehrere Kernsymptome des FMS (Schmerz.…”
Section: Stellenwert Psychotherapeutischer Verfahrenunclassified
“…Aufgrund der eingeschränkten Verfügbarkeit von ärztlichen und psychologischen Psychotherapeuten zur Behandlung chronischer Schmerzen, ist der Wirksamkeitsnachweis von internetbasierten psychologische Verfahren von Interesse [46]. Diese Behandlungen stehen in Deutschland noch nicht in der Routineversorgung zur Verfügung.…”
Section: Stellenwert Psychotherapeutischer Verfahrenunclassified